Seroepidemiology of selected transboundary animal diseases in goats in Zambia - Lysholm, S.; Lindahl, Johanna F.; Dautu, G.; Johansson, E.; Bergkvist, P.K.; Munyeme, M.; Wensman, Jonas Johansson (Elsevier, 2022)
Transboundary pathogens of goats present significant constraints to the livelihoods of millions of farmers in countries such as Zambia. Consequently, this study aimed to investigate the seroprevalence of Mycoplasma capricolum subsp. capripneumoniae (Mccp), foot and mouth disease virus (FMDV), Brucella spp., Crimean Congo haemorrhagic fever virus (CCHFV), and Rift Valley fever virus (RVFV) in Zambian goats. Another aim was to identify associations between seroprevalence and different predictor variables, such as trade and border proximity. From September to October 2019, 962 serum samples were collected from goats in seven Zambian districts, four of which have an international border while the remaining three do not. A questionnaire survey was conducted with each household, focusing on trade routines, management strategies and herd disease history. Animal-level seroprevalence adjusted for herd-level clustering was 8.2 % (95 % confidence interval [CI] 7.5–9.0) for Mccp, 12.9% (95% CI 12.0–13.7) for FMDV, 13.0 % (95% CI 12.1–13.9) for Brucella spp., 3.3 % (95% CI 2.8–3.7) for CCHFV, and 0.4 % (95 % CI 0.3–0.7) for RVFV. The association between herd-level seroprevalence and border proximity and trade appeared negligible, with the exception of selling goats at least twice a year which was identified as a potential risk factor for Brucella spp. (OR 4.1, 95 % CI 1.1–16.0, p = 0.040). In addition, a positive association between herd-level seroprevalence of FMDV and a herd size of 21 goats or more (OR 3.3, 95 % CI 1.0–11.1, p = 0.049) was detected. Also, positive associations between animal-level seroprevalence of Brucella spp. and increasing age (OR 7.7, 95 % CI 1.5–40.7, p = 0.016), and CCHFV and keeping pigs in the household (OR 2.7, 95 % CI 1.0–7.1, p = 0.044), were found. For FMDV (OR 3.8, 95 % CI 1.4–10.9, p = 0.011) and Brucella spp. (OR 4.5, 95 % CI 1.2–17.3, p = 0.031) on the other hand, animal-level seroprevalence was significantly higher in households without pigs. To the best of the authors’ knowledge, this is the first study to describe the presence of antibodies for CCPP and CCHF in the Zambian goat population. While the association between seroprevalence and trade and border proximity generally appeared negligible, it is recommended that their influence is further evaluated in future studies, preferably through in-depth longitudinal studies incorporating impacts of different biosecurity measures and trade variations, linked to for example seasonality and trade peaks.